Proposed Model for Estimating the Total Social Demand for Health Services in Lattakia Governorate between 2003 and 2018 (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The demand for health services is of great importance as it is linked to the social aspect, which is the health status of citizens in a country, and it is from this importance that our current study focusing on a very important problem related to the ability to estimate the total social demand for health services was chosen. The study was the reality of social demand On health services in the public sector in Lattakia Governorate is one of the most important objectives of the study, in addition to studying the reality of social demand for health services in the private sector in Lattakia Governorate, and working on proposing a model for estimating social demand for health services in the public and private sectors.An analytical descriptive approach has been used, and at the end of the study the study reached an important set of results related to the port of the model and the estimation of social demand for health services in pharmacies, clinics and laboratories based on a questionnaire distributed to families in Latakia, in addition to the opinion of specialists from doctors, pharmacists, laboratory owners, and specialists At the Doctors Syndicate, the Dental Association, and the Pharmacists Syndicate. The health insurance system applied to workers in the country also contributed to increasing the demand for medical treatment in private sector clinics, as well as increasing social demand for health services provided in public hospitals during the study period, and the current crisis and the war on Syria have increased the demand for health services in general in Lattakia Governorate.